Realising the potential of natural water retention measures in catchment flood management: trade‐offs and matching interests. Issue 1 (29th September 2016) - Collentine, D.; Futter, M.N.
Abstract : Natural water retention measures (NWRM) are a multifunctional form of green infrastructure that can play an important role in catchment‐scale flood risk management. While green infrastructure based on natural processes is increasingly recognised as being complementary to traditional flood control strategies based on grey infrastructure in urban areas, there are a number of outstanding challenges with their widespread uptake. At a catchment scale, it is widely accepted that NWRM in upstream areas based on the concept of 'keeping the rain where it falls' can help reduce the risk of downstream flooding by enhancing or restoring natural hydrological processes including interception, evapotranspiration, infiltration, and ponding. However, both the magnitude of flood risk reduction and the institutional structures needed for widespread uptake of NWRM are inadequately understood. Implementing NWRM can involve trade‐offs, especially in agricultural areas. Measures based on drainage management and short rotation forestry may help 'keep the rain where it falls' but can result in foregone farm income. To identify situations where the implementation of NWRM may be warranted, an improved understanding of the likely reductions in downstream urban flood risk, the required institutional structures for risk management and transfer, and mutually acceptable farm compensation schemes are all needed.